Dance and power in bolivar’s colombia (2012)
Far from being a frivolous and banal activity, dance isa powerful political weapon in times of war and peace.Trying to prove this assertion, we discuss specificallythe use of dance in the period from the beginning of theindependence process in New Granada and Venezuelain 1810, to the end of the Colombian project with thedeath of Simon Bolivar in 1830. To do that, we referto the theories of political economy of music of JacquesAttali and the imposed musical events concept of VéroniqueHébrard.